'Was the Cold War Avoidable? Did the West Seek to Win It?: A Contribution to the Debate'. Issue 2 (3rd April 2021) - Lukes, Igor
ABSTRACT: This article tackles two of the major questions in later twentieth-century international history, the origins and the end of the Cold War. Historians traditionally assumed that Moscow was determined from the outset to Sovietise Eastern Europe, once liberated from Nazism, and that this made the later confrontation with the Western powers inevitable. It will be shown here that the idea to install Moscow-friendly regimes in a Europe destroyed by war had been formulated by Kremlin officials already a decade earlier. The article also argues that the Western alliance became comfortable with the status quo it had previously denounced, and that it was reluctant to upset the East-West equilibrium of later years. In the aftermath of 1989, several Western politicians have claimed the laurels of victory over Communism, but it was the Soviet bloc countries who liberated themselves, despite pleas of officials in London, Washington, Paris, and Bonn to slow down or even suspend their reforms.